(untitled) (BIRDEM Medical Journal, 2017)
Graves disease (GD) is an autoimmune disorder of the thyroid gland resulting from dysregulation of the immune system against this important endocrine gland. The disease is characterized by hyperthyroidism and presence of circulation auto antibody which stimulates the Thyroid Hormone Receptor(TSHR). The auto antibody is also responsible for goiter and other extra-thyroidal manifestation like ophthalmic, dermatological and others. Vitamin D (Vit.-D) deficiency is reported to link with variety of autoimmune diseases. However the relation between thyroid autoimmunity of Graves disease and Vitamin D deficiency is still not very clear. But in some studies10-12, it was found that there is strong correlation between thyroid autoimmunity and vitamin D 1,25-(OH) deficiency in newly diagnosed GD. It was found < 15 pmol/L. In one study it was found <12.5pmol/ L. According to definition of insufficiency or deficiency most of the Author agreed to describe insufficiency when Vit D level is less than 30pmol/L and deficient when less than 20 pmol/L. Vitamin D Receptor gene polymorphism is also associated with increased risk of Graves (4D) disease and higher volume of goiter. In other studies it was found that, the increased thyroid antibody titer was associated with Vitamin D deficiency. Some other studies showed that, treatment with Vitamin D in GD there is significant early improvement of the diseases. Meta-analysis showed low Vitamin D was also associated with higher risk of development of GD. Moreover, hyperthyroidism leading to osteoporosis in GD is also associated with low Vitamin D level and improves by treatment with Vitamin D. However, whether Vitamin D deficiency or insufficiency favors the onset of GD or supplementation of Vitamin D has any beneficial effect, needs further research. Birdem Med J 2017; 7(2): 160-163